Biofertilizers in horticultural crops - Cavalcante, Lourival Ferreira; Bezerra, Francisco Thiago Coelho; Souto, Antônio Gustavo de; Bezerra, Marlene Alexandrina Ferreira; Lima, Geovani Soares de; Gheyi, Hans Raj; Pereira, Jorge F. da Silva; Beckmann-Cavalcante, Márkilla Zunete (Comunicata Scientiae, 2019)
Bovine manure biofertilizers can exert physical, chemical, and biological effects on the soil and the phytoprotective, physiological, and productive actions in horticultural crops. The literature review was performed to compile information on the production, uses, and effects of bovine manure biofertilizers on soil properties and plants. Biofertilizers are produced by organic components, minerals, and inoculants. Among the organic sources, the bovine manure is the most used. The fermentation of the bovine manure in water constitutes the Vairo biofertilizer, the most employed in Brazilian horticulture. With the chemical enrichment of this preparation came the Supermagro, Agrobio, and Agrobom biofertilizers. In the soil, it can act in the improvement of soil fertility, physical properties, and in the diversity and abundance of the biota. Also, it can act in control of pests and diseases, leaf composition concerning macro and micronutrients, and in the production and post-harvest quality of horticultural crops. Therefore, this review describes the preparation, chemical composition, and utilization of bovine manure biofertilizers in both soil and plants, offering perspectives of research on the formulations, application, and effects of these inputs on horticultural species.